2022
DOI: 10.3390/e24081151
|View full text |Cite
|
Sign up to set email alerts
|

Design of DNA Storage Coding with Enhanced Constraints

Abstract: Traditional storage media have been gradually unable to meet the needs of data storage around the world, and one solution to this problem is DNA storage. However, it is easy to make errors in the subsequent sequencing reading process of DNA storage coding. To reduces error rates, a method to enhance the robustness of the DNA storage coding set is proposed. Firstly, to reduce the likelihood of secondary structure in DNA coding sets, a repeat tandem sequence constraint is proposed. An improved DTW distance const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…However, as for the problem of the hairpin structure generation in DNA sequences, this problem can only be addressed to a certain extent by using the proposed constraints but cannot be completely solved. In [ 23 ], Li et al proposed a repeat tandem sequence constraint and improved the DTW distance constraint. The repeat tandem sequence constraint was used to address the problem of the secondary structure arising from successively repeated occurrences of coding sequences, and the improved DTW distance constraint was used to address the problem of inaccurate assessment of the overall similarity between sequences obtained under the traditional distance constraint.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, as for the problem of the hairpin structure generation in DNA sequences, this problem can only be addressed to a certain extent by using the proposed constraints but cannot be completely solved. In [ 23 ], Li et al proposed a repeat tandem sequence constraint and improved the DTW distance constraint. The repeat tandem sequence constraint was used to address the problem of the secondary structure arising from successively repeated occurrences of coding sequences, and the improved DTW distance constraint was used to address the problem of inaccurate assessment of the overall similarity between sequences obtained under the traditional distance constraint.…”
Section: Discussionmentioning
confidence: 99%
“…The focus is on solving the problem of local base appearance. This study compared the lower bound data from the coding set with the results presented in [ 23 ] and found that the results presented in [ 23 ] show a good advantage in terms of finding the lower bounds of the coding sets of long sequences. However, for the lower bounds of the coding sets of shorter sequences, the results presented in this study are better than the results in [ 23 ] and [ 45 ], and some of the data presented in the study conducted by Li et al are inferior to those presented in [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations